2014
DOI: 10.1111/exd.12417
|View full text |Cite
|
Sign up to set email alerts
|

Distinct melanoma types based on reflectance confocal microscopy

Abstract: Distinct melanoma types exist in relation to patient characteristics, tumor morphology, histopathologic aspects and genetic background. A new diagnostic imaging tool, reflectance confocal microscopy (RCM), allows in vivo analysis of a given lesion with nearly histologic resolution while offering a dynamic view of the tissue in its 'natural' environment. The aim of this study was to analyse cell morphology of consecutive melanomas as they appear on RCM and to correlate morphology with tumor and patient characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 43 publications
8
77
0
3
Order By: Relevance
“…11 These findings reinforce the hypothesis that at least 2 different routes of melanoma development exist. The first was associated with multiple nevi, predominance on the trunk, and younger age at onset, characterized via RCM by round cell pattern.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…11 These findings reinforce the hypothesis that at least 2 different routes of melanoma development exist. The first was associated with multiple nevi, predominance on the trunk, and younger age at onset, characterized via RCM by round cell pattern.…”
supporting
confidence: 72%
“…2, [6][7][8][9][10] Recently, 4 distinct melanoma phenotypes on RCM were described as follows: dendritic cell, round cell, dermal nest, and combined melanomas. 11 The authors found that melanomas with a predominant population of dendritic cells were thinner by Breslow index, and melanomas typified by roundish melanocytes or dermal nests were smaller but thicker by Breslow index. 11 The purpose of this study was to correlate morphologic RCM patterns with clinical data, genetic variants, dermoscopic features, and histologic criteria in the context of patients with multiple primary and familial melanomas.…”
Section: 3mentioning
confidence: 97%
“…However, RCM is an important noninvasive diagnostic tool that has enabled satisfactory characterization of melanocytic and nonmelanocytic skin lesions. Numerous articles describe its utility in defining cell population and morphology in melanomas, which makes it a useful supplement to clinical and histologic findings, with which RCM shows precise correlates [10][11][12][13][14]. In addition, interestingly, it was used for the follow-up of changing moles in patients receiving treatment with BRAF inhibitors for metastatic melanomas [15].…”
Section: Discussionmentioning
confidence: 99%
“…For the evaluation of dermoscopic and confocal images, both semiquantitative evaluations and quantitative measurements were obtained. Two expert dermoscopists and confocalists evaluated six dermoscopic patterns and six RCM parameters that were selected to better characterize invasive melanomas from the wider group of known dermoscopic and RCM known descriptors (Table 1) [10]. Absolute and relative frequencies were calculated for each parameter to characterize BRAFp.V600E mutated melanomas.…”
Section: Methodsmentioning
confidence: 99%
“…One of the critical barriers in early skin-cancer detection is the lack of reliable non-invasive techniques [7] that can detect the cancer at an early stage with high detection probability (i.e., the probability of correctly detecting a malignant lesion) and low false-alarm probability (i.e., the probability of declaring a benign lesion as malignant). Non-invasive techniques for skin-cancer detection include multispectral (MS) imaging [8][9][10], digital dermatoscopy and videodermatoscopy (sequential digital dermatoscopy) [11,12], reflectance-mode confocal microscopy [13], ultrasound [14,15], laser Doppler perfusion imaging [16], and optical coherence tomography (OCT) [17,18]. Each technology presents some restrictions and limitations to non-invasively detect skin cancer with high detection probability and low false-alarm probability.…”
Section: Introductionmentioning
confidence: 99%